Representasi Komunikasi Interpersonal Orang Tua dan Anak dalam Film Animasi "Inside Out" Karya Pete Docter - Emerald, Ananda Mirza; E. Rizky Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Emotions are normal reactions that occur in humans. Emotional is closely related to the expression of feelings. Emotional is a trait that exists because of emotions. In general, emotions are states that cannot be controlled. Emotional feelings are a condition that can affect daily life. However, emotional reactions are something that can also be controlled. One of the studio houses from the United States, Pixar Animation Studios, wants to try to understand more about how emotions can be formed from an early age through animated films. This research analyzes the representation of interpersonal communication between parents and children in the animated film "Inside Out". This research uses Ferdinand De Saussure's semiotic analysis model by analyzing through two stages of marking, namely denotation and connotation. The collection process is carried out by watching the animated films directly and also taking references from third parties. The results of this research show that there are problems that make interpersonal communication between parents and children in the animated film "Inside Out" not run well because the child cannot express emotions and feelings, parents feel guilty towards their children, and this animated film is one a tool that can be used as a learning medium.